Structural and Nanotribological Properties of a BODIPY Self-Assembly - Tan, Shanchao; Luo, Wendi; Zhang, Yongjie; Ren, Xiang-Kui; Liu, Yuhong; Chen, Zhijian; Zeng, Qingdao (Frontiers in Chemistry, 2021)
Boron-dipyrromethenes (BODIPY) are promising functional dyes, whose exceptional optical properties are closely related to their supramolecular assembly. Herein, the self-assembly of a BODIPY derivative functionalized with uracil groups is explicitly and thoroughly investigated by using scanning tunneling microscopy (STM). Based on the simulation and calculation by density functional theory (DFT) method, it can be concluded that the construction of ordered self-assembly structure is attributed to the formation of hydrogen bonds between uracil groups. Moreover, the nanotribological property of the self-assembly on HOPG surface is measured by using atomic force microscopy (AFM). The effort on self-assembly of the BODIPY derivative could enhance the understanding of surface assembly mechanism.